FUNGSI MANAJEMEN BERBASIS SEKOLAH DI ERA NEW NORMAL SEKOLAH DASAR ISLAM TERPADU (SDIT) LUKMANUL HAKIM - Yurni Rahman; Fandi H. Binggo; Windi Virgina Ali (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2024)
This study aims to determine the function of school-based management in the new normal era of SD Islam Terpadu Lukmanul Hakim, in terms of curriculum and learning, students, educators and education staff. This study uses qualitative research methods with data collection techniques through observation, interviews and documentation derived from primary and secondary data. The results showed that the management of the learning curriculum, students, educators and education staff are in accordance with the management function. It can be seen from planning, organizing, supervising and coaching which is quite good to improve the quality of education